Pengaruh Employer branding dan Kepuasan Kerja terhadap Retensi Karyawan di PT. Sinar Galesong Pratama - Rusni, Rusni; Dipoatmodjo, Tenri Sayu Puspitaningsih; Hamka, Rezky Amalia; Musa, Chalid Imran; Kurniawan, Agung Widhi (Peneliti.net, 2026)
This research aims to determine the influence of employer branding and job satisfaction on employee retention at PT. Sinar Galesong Pratama. The study uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to 80 respondents who are employees of PT. Sinar Galesong Pratama. The data were analyzed using multiple linear regression to examine the effect of the independent variables (employer branding and job satisfaction) on the dependent variable (employee retention). The results show that, partially, employer branding and job satisfaction have a positive and significant effect on employee retention at PT. Sinar Galesong Pratama. Furthermore, simultaneously, employer branding and job satisfaction also have a significant effect on employee retention at PT. Sinar Galesong Pratama.